PMO-093 MRNA profiling of the cancer degradome in oesophago-gastric adenocarcinoma. (28th May 2012) - Baren, J P; Stewart, G D; Stokes, A; Gray, K; Pennington, C J; Deans, C; Paterson-Brown, S; Riddick, A C; Edwards, D R; Fearon, K C; Ross, J A; Skipworth, R J
Abstract : Introduction: Degradation of the extracellular matrix is fundamental to tumour development, invasion and metastasis. Several protease families have been implicated in the development of a broad range of tumour types, including oesophago-gastric (OG) adenocarcinoma. The aim of this study was to analyse expression levels of all core members of the cancer degradome in OG adenocarcinoma, and to investigate the relationship between expression levels and tumour/patient variables associated with poor prognosis. Methods: Comprehensive expression profiling of the protease families [matrix metalloproteinases (MMPs), members of the ADAM metalloproteinase-disintegrin family (ADAMs)], their inhibitors [tissue inhibitors of metalloproteinase (TIMPs)], and molecules involved in the c-Met signalling pathway, was performed using quantitative real-time reverse transcription PCR in a cohort of matched malignant and benign peri-tumoural OG tissue (n=25 patients). Data were analysed with respect to clinico-pathological variables (tumour stage and grade, age, sex and pre-operative plasma C-reactive protein level). Results: Gene expression of MMP1, 3, 7, 9, 10, 11, 12, 16 and 24 was upregulated by factors greater than fourfold in OG adenocarcinoma samples compared with matched benign tissue (p<0.01). Expression of ADAM8 and ADAM15 correlated significantly with tumour stage (p=0.048 and p=0.044), and ADAM12 expression correlated with tumour grade (p=0.011). Conclusion: This study represents the first comprehensive quantitative analysis of the expression of proteases and their inhibitors in human OG adenocarcinoma. These findings implicate elevated ADAM8, 12 and 15 mRNA expression as potential prognostic molecular markers. Competing interests: None declared.